القواعد والضوابط الفقهية المستنبطة من كتاب التوضيح للشيخ خليل - دهيني عبد القادر; بن حرمة عبدالله; بوخاتم مصطفى الهاشمي; د/بوفاتح الطيب (جامعة عمار ثليجي الاغواط, 2023)
هذه الدراسة تهدف إلى جمع ودراسة القواعد والضوابط الفقهية في مسألة النكاح، وترتكز على استخلاصها من كتاب التوضيح للشيخ خليل. تسعى الدراسة إلى تأصيل المسائل الفقهية المتعلقة بالنكاح وتحليلها بناءً على القواعد والضوابط المستنبطة من هذا الكتاب. على سبيل المثال، من بين هذه القواعد الفق هية هو "أن الأصل في النكاح هو الحلال"، ومن الضوابط الفقهية مثال "أنه عندما يتم عقد زواج صحيح بين الزوجين، تُحرم المرأة الخاضعة للعقد على أبي الزوج وأجداده وولده وولد ولده إلى الأبد، وتحرم أمها أيضًا إلى الأبد بسبب هذا العقد". من النتائج المستنتجة من الدراسة أن لكل قاعدة أو ضابط فقهي دليل يستند إليه من الكتاب أو السنة النبوية، وأن القواعد والضوابط الفقهية تعتبر حجة قوية للمسلمين لاستنباط الأحكام الشرعية، وأن القاعدة والضابط ليسا نفس الشيء، وإنما الضابط يعتبر تفصيلًا أو استنتاجًا محددًا يستند إلى القاعدة الفق هية العامة . Summary This study aims to collect and study the jurisprudential rules and regulations in the chapter of marriage (Nikah) by Sheikh Khalil, based on the following problem: What are the jurisprudential rules and regulations derived by scholars from the book "Tawdih" by Sheikh Khalil in the chapter of marriage as a model? Additionally, what is the foundation for establishing the jurisprudential issues in the chapter of marriage? One of these rules is "the default ruling regarding sexual intercourse is prohibition", and one of the regulations is "every valid marriage contract prohibits the wife, through that contract, from the husband's father, ancestors, son, grandson, and their respective offspring forever, and also prohibits her mother forever due to that contract". One of the conclusions drawn is that every jurisprudential rule or regulation has an interpretation based on evidence from the Quran or Sunnah, and that rules and regulations serve as evidence in deriving Islamic rulings, and that a rule and a regulation are not the same thing